(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
This cross sectional study was conducted among the children aged 18 years and below at korail slum, near Gulshan Lake, Banani, Dhaka during March to June 2007 to ascertain the pattern of injuries and the risk factors associated with those injuries. Data were collected using cluster sampling technique. The total numbers of children under study in the surveyed house-holds were 486 and out of them 210 were injured. The prevalence of injury was, therefore, 43.2% or 432 per 1000 children. Nearly half (47%) of the participants were between 10-15 years of age and only about 2% were 15-18 years. The mean age was 8.8 ±3.4 years and the lowest and highest ages were 6 months and 17 years respectively. Male-female ratio was almost 1:1 and injury rate did not vary at all with respect to sex. The highest injury rate was observed among <5 yrs children (49%) and the lowest among those aged 15-18 yrs (39%). However, variation in age specific injury rates was not remarkable. The highest number of child injury was due to burn (33%), followed by road accident (29%) and occupational injury (14%). Other causes of child injuries were fall on the street (8%), animal bite (4%), fall from tree (1.5%), drowning (2%), fall from roof (3%), electric burn (1.5%), poisoning (1%) and chemical burn (0.5%) respectively. The overall high rate of prevalence of child injury and major causes (burn, road traffic accident, occupational injury) suggest for launching preventive strategy. Further in depth studies are recommended. DOI: http://dx.doi.org/10.3329/jdnmch.v18i1.12235 J. Dhaka National Med. Coll. Hos. 2012; 18 (01): 24-28